2021
DOI: 10.1073/pnas.2026271118
|View full text |Cite
|
Sign up to set email alerts
|

Conventional NK cells and tissue-resident ILC1s join forces to control liver metastasis

Abstract: The liver is a major metastatic target organ, and little is known about the role of immunity in controlling hepatic metastases. Here, we discovered that the concerted and nonredundant action of two innate lymphocyte subpopulations, conventional natural killer cells (cNKs) and tissue-resident type I innate lymphoid cells (trILC1s), is essential for antimetastatic defense. Using different preclinical models for liver metastasis, we found that trILC1 controls metastatic seeding, whereas cNKs restrain outgrowth. W… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 55 publications
2
76
0
Order By: Relevance
“…In the current study, NK cells have been found to be compromised in several cancer types, and skewed NK cells contributes to cancer progression via tumor escape and immunosuppression. Downregulation of activating receptor expression on NK cells and impaired NK function are common mechanisms of immune evasion in cancer, and have been associated with tumor progression [28]. Competitive interactions between TIGIT (T cell immunoreceptor with Ig and immunoreceptor tyrosine-based inhibitory motif [ITIM] domains) and CD226 receptors with cognate ligands, such as nectins and poliovirus receptor (PVR), play a critical role in TIGIT-driven immune suppression, and anti-TIGIT therapy is designed to reverse this suppression by inhibiting TIGIT-PVR binding [29].…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, NK cells have been found to be compromised in several cancer types, and skewed NK cells contributes to cancer progression via tumor escape and immunosuppression. Downregulation of activating receptor expression on NK cells and impaired NK function are common mechanisms of immune evasion in cancer, and have been associated with tumor progression [28]. Competitive interactions between TIGIT (T cell immunoreceptor with Ig and immunoreceptor tyrosine-based inhibitory motif [ITIM] domains) and CD226 receptors with cognate ligands, such as nectins and poliovirus receptor (PVR), play a critical role in TIGIT-driven immune suppression, and anti-TIGIT therapy is designed to reverse this suppression by inhibiting TIGIT-PVR binding [29].…”
Section: Discussionmentioning
confidence: 99%
“…'Immune Profiling in Multiple Myeloma' (NCT04135079) does not state in its aims that it will be looking at ILCs specifically. The impact of targeting ILCs should not be underestimated and is only beginning to come into view [146]. Unravelling the immunology of ILCs in MM is likely to provide better options for the treatment of MM and other malignancies.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Thus, so far, there are no specific mouse models to precisely investigate the role of liver ILC1 in HCC development and progression. Recent investigations using preclinical models of liver metastasis suggest that ILC1 are essential to control metastatic seeding, whereas NK cells restrain tumor outgrowth [302].…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%